Síntese e avaliação de 1-(2-(2,3-diidrobenzofuranil)metil)piperazinas potencialmente ligantes de receptores histaminérgicos H4 - Correa, Michelle Fidelis [UNIFESP] (2015)
Histamine is one of the most important chemical mediators of the body. Involved in numerous physiological and pathological conditions, their effects are produced by interaction with histamine G-protein coupled receptors (GPCRs). So far it was described four histamine receptors (H1, H2, H3 and H4) differing among them in cell signaling mechanisms. Since its discovery, the H4 receptor (H4R) has been the focus of much attention. It is expressed primarily in immune cells of hematopoietic origin and, therefore has strong relationship with inflammatory and immune responses, and consequently with the pathophysiology of immuno-inflammatory disorders. Thus, the H4R is considered to be potential target for the development of new chemical entities. Considering the therapeutic potential of H4R ligands, this work aimed to synthesize 1-(2-(2,3-dihydrobenzofuranyl)methyl)piperazines inedited and evaluate their binding activity in H4R as well as H3R to analyze the selectivity towards the two receptors and obtaining compounds with increased selectivity index to H4R. Series of compounds were synthesized using iodociclization reaction, yielding 2-(iodomethyl)-2,3-dihydrobenzofuran, followed by halogen substitution with N-substituted piperazines, reaching the final compounds (LINS01001, LINS01003, LINS01004 e LINS01005). The biological activity was performed by displacement of [3H]-histamine from H3R and H4R to obtain the binding constant (Ki) from the IC50 values using the Cheng-Prussoff equation. The results indicated that the compounds had mild affinity for both receptors, exhibiting Ki values in the micromolar range. However, the compounds demonstrate different selectivity. The phenyl group, present in LINS01005, took good interaction, but non specific between the receptors (H4R Ki 28 µM; H3R Ki 17 µM)and alkyl groups give more selective H3R, as observed with compounds LINS01003 (H3R Ki 25 µM) e LINS01004 (H3R Ki 7 µM). Moreover, it was noted that the aromaticity of the core is important for good affinity to both receptor as well as the presence of a hydrophobic substituent attached at the N4-piperazine, since the molecule unsubstituted LINS01001, had the lowest affinity and Ki values for both receptor have not been determined. The results obtained in this work contribute directly to the development of new H4R ligands. It is intended to continue with future design and structural optimization of the proposed compounds to obtain higher affinity and selectivity.